Social comparison and life satisfaction in social media: The role of mattering and state self-esteem - Patrick P. T. Sim; Kususanto Ditto Prihadi (International Journal of Public Health Science (IJPHS), 2020)
The overarching aim of this study is to explain how comparing self to others in social media might predict one’s sense of life satisfaction. In order to achieve that, we test the hypothesis that mattering and state self-esteem play a serial mediation that explains the link between social comparison in social media and life satisfaction. One hundred and forty-seven participants’ ages between 18 to 35 were recruited to participate in this research and were asked to fill up the Iowa-Netherlands Comparison Orientation Measure, General Mattering Scale, State Self-Esteem Scale and Riverside Life Satisfaction Scale questionnaires. Bias-free Bootstrap Method with 5000 sample has been conducted to analyze the relationship among the variables, and the results suggested that the overall model of the predictor significantly contributed to life satisfaction. Nevertheless, because social comparison did not predict the sense of mattering, serial mediation did not occur as per hypothesized. Our supplementary analyses indicated that state self-esteem fully mediated the contribution of mattering on life satisfaction. Implication, limitation and suggestions are discussed at the end of the paper.